Maximizing the Potential of Longitudinal Cohorts for Research in Neurodegenerative Diseases: A Community Perspective - Moody, Catherine J.; Mitchell, Derick; Kiser, Grace; Aarsland, Dag; Berg, Daniela; Brayne, Carol; Costa, Alberto; Ikram, Mohammad A.; Mountain, Gail; Rohrer, Jonathan D.; Teunissen, Charlotte E.; van den Berg, Leonard H.; et al. (Frontiers in Neuroscience, 2017)
Despite a wealth of activity across the globe in the area of longitudinal population cohorts, surprisingly little information is available on the natural biomedical history of a number of age-related neurodegenerative diseases (ND), and the scope for intervention studies based on these cohorts is only just beginning to be explored. The Joint Programming Initiative on Neurodegenerative Disease Research (JPND) recently developed a novel funding mechanism to rapidly mobilise scientists to address these issues from a broad, international community perspective. Ten expert Working Groups, bringing together a diverse range of community members and covering a wide ND landscape (Alzheimer’s, Parkinson’s, frontotemporal degeneration, amyotrophic lateral sclerosis, Lewy-body and vascular dementia) were formed to discuss and propose potential approaches to better exploiting and coordinating cohort studies. The purpose of this work is to highlight the novel funding process along with a broad overview of the guidelines and recommendations generated by the ten groups, which include investigations into multiple methodologies such as cognition/functional assessment, biomarkers and biobanking, imaging, health and social outcomes, and pre-symptomatic ND. All of these were published in reports that are now publicly available online.